Extinct, obscure or imaginary: The lizard species with the smallest ranges. Issue 2 (23rd November 2017) - Meiri, Shai; Bauer, Aaron M.; Allison, Allen; Castro‐Herrera, Fernando; Chirio, Laurent; Colli, Guarino; Das, Indraneil; Doan, Tiffany M.; Glaw, Frank; Grismer, Lee L.; Hoogmoed, Marinus; Kraus, Fred; et al.
Abstract: Aim: Small geographic ranges make species especially prone to extinction from anthropogenic disturbances or natural stochastic events. We assemble and analyse a comprehensive dataset of all the world's lizard species and identify the species with the smallest ranges—those known only from their type localities. We compare them to wide‐ranging species to infer whether specific geographic regions or biological traits predispose species to have small ranges. Location: Global. Methods: We extensively surveyed museum collections, the primary literature and our own field records to identify all the species of lizards with a maximum linear geographic extent of <10 km. We compared their biogeography, key biological traits and threat status to those of all other lizards. Results: One in seven lizards (927 of the 6, 568 currently recognized species) are known only from their type localities. These include 213 species known only from a single specimen. Compared to more wide‐ranging taxa, they mostly inhabit relatively inaccessible regions at lower, mostly tropical, latitudes. Surprisingly, we found that burrowing lifestyle is a relatively unimportant driver of small range size. Geckos are especially prone to having tiny ranges, and skinks dominate lists of such species not seen for over 50 years, as well as of species known only from their holotype. Two‐thirds of these species have no IUCN assessments, and at least 20 are extinct. Main conclusions: Fourteen per cent of lizard diversity is restricted to a single location, often in inaccessible regions. These species are elusive, usually poorly known and little studied. Many face severe extinction risk, but current knowledge is inadequate to properly assess this for all of them. We recommend that such species become the focus of taxonomic, ecological and survey efforts.